Hepatoprotective Activity of Homeopathic Formulation AlphaTM-Liv Drops in Rat Model (Advancements in Homeopathic Research, 2024)
Liver diseases pose a serious health  challenge in India, impacting roughly 20% of  the population and standing as a leading cause of  mortality. Traditional treatments often fall short,  especially in rural areas with limited healthcare access.  Homeopathy in general has shown its effectiveness.  This study investigates the hepatoprotective activity  of Alpha™-Liv Drops, a homeopathic formulation,  to explore its potential treatment option for liver  diseases in the Indian healthcare landscape.
Keywords: Liver diseases; hepatoprotective; Alpha™-Liv Drops; liver function markers; antioxidants; homeopathic treatment